Prednisolone and Mustine in Prevention of Tumour Swelling during Pulmonary Irradiation. Issue 5799 (26th February 1972) - Cameron, S. J.; Grant, I. W. B.; Pearson, J. G.; Marques, C.
Abstract : Ventilatory function declines during the early stages of irradiation for bronchial carcinoma. This decline is potentially dangerous if the tumour narrows the trachea or both main bronchi. The protective effect of preliminary treatment with prednisolone or mustine before irradiation was studied in 88 patients by serial estimations of forced expiratory volume and forced vital capacity. Twenty-three patients received prednisolone by mouth, 24 had mustine intravenously, and 41 had no preliminary treatment. Both prednisolone and mustine prevented a significant decline in ventilatory function due to tumour swelling, prednisolone being marginally superior. It is concluded that all patients at risk should be treated with oral prednisolone, 20 mg daily, for one day before and two days after the first fraction of irradiation.